FEATURES OF THE ORGANIZATION OF ARTISTIC AND DESIGN ACTIVITY OF JUNIOR SCHOOLCHILDREN - Olesia Makoviichuk; Alona Shulha ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article analyzes the theoretical aspects of art and design activities, considers the features of the integrative organization of art and design activities of students in the lessons of fine arts and technology in primary school. Artistic and project activities of junior schoolchildren are realized through the disciplines of fine arts and labor education (technology) in primary school. The concept of "artistic and design activity" is analyzed through the prism of the concepts of "activity", "artistic activity". The following are considered: interconnected structural components of artistic design, types of activity and types of tasks aimed at the implementation of artistic design activities of junior schoolchildren. The article emphasized the potential of an integrated combination in primary school of fine arts and labor training (technology) for art and design activities of junior high school students.